Le singe-soldat de Woyzeck - Élisabeth Hamm (Recherches Germaniques)
In Woyzeck, an unfinished and fragmentary play written by Georg Büchner (1837), the question of anthropomorphism is raised when a monkey enters the stage at the beginning of the fair scene (H1,1). Through the phenomenon of theatre within the theatre, the monkey disguised as a soldier symbolizes the fair’s audience, composed mainly of soldiers. He not only takes on human physical characteristics, by standing up and wearing a military uniform, but he also mimics human behaviour by bowing, shooting or playing music. This article focuses on the representation of this case of anthropomorphism in Werner Herzog’s film (1979), as well as its staging in two contemporary performances, one by Stéphane Braunschweig (1999) and one by Leander Haußmann (2014). The analysis of performances will allow us to see how the imaginary power of “human” animals enhances the potentialities of stage practices and how the scenography enhances the representation of anthropomorphism. Anthropomorphism can be considered as an aesthetic issue participating, in Woyzeck’s case, in a critique of society.